Implementing new consent procedures for schools-based human papillomavirus vaccination: a qualitative study. (2nd April 2021) - Audrey, Suzanne; Evans, Karen; Farr, Michelle; Ferrie, Joanne; Yates, Julie; Roderick, Marion; Fisher, Harriet
Abstract : Background: The requirement for written parental consent for school-based human papillomavirus vaccination programme in England can act as a barrier to uptake for some young women, with the potential to exacerbate health inequities. Aims: To consider the practicalities and implications of implementing new consent procedures, including parental telephone consent and adolescent self-consent, in two local authority areas in the southwest of England. Methods: Digitally recorded, semi-structured interviews were conducted with 53 participants, including immunisation nurses, school staff, young people, and parents. All interviews were fully transcribed and thematic analysis was undertaken. Results: Parental telephone consent was welcomed by the immunisation nurses, parents, and young women in the study. Adolescent self-consent was rare. Greater understanding of the barriers to uptake outside of mainstream school-based sessions is needed to further address inequalities in uptake. Conclusions: The new procedures generally worked well but some important barriers to vaccination uptake remain.